Leiomyoma of Oral Cavity: Case Report and Literature Review - NAMDAR PEKİNER, FİLİZ MEDİHA (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Leiomyoma is a benign smooth muscle tumor that can be observed at any region but is mostly observed in the female genital tract. Although leiomyomas are uncommon in the oral cavity, they are usually observed on the lips, tongue, and palate. Here we present a case report of leiomyoma in a female patient along with the literature review. A 35-year-old Turkish female presented with a 1-year history of a well-delineated, asymptomatic, and soft mass on the vestibule alveolar mucosa of the right mandibular molar region. Under local anesthesia, excisional biopsy was performed and the specimen was sent for histopathological examination. The histopathological diagnosis was leiomyoma. Based on clinical appearance, it is very challenging to distinguish a leiomyoma from other mesenchymal-origin tumors. Histological analysis determined the final diagnosis of oral leiomyoma, and surgery was performed because it was the only option for the treatment of these lesions.
Keywords: Leiomyoma; benign tumor; oral cavity; VASCULAR LEIOMYOMA